Aplikasi Dispensasi Berbasis Web Menggunakan Metode Waterfall pada SMKS TI Airlangga Samarinda - Bella Marettiani Sulaiman; Fahrullah; Riyayatsyah (LPPM Universitas Nias Raya, 2024)
The problem at SMKS IT Airlangga is that the student dispensation process is still carried out using dispensation form paper and students who wish to apply for a permit must visit the student waka kesiswaan in the room, this takes time. the purpose of this research is to have a dispensation application at SMKS IT Airlangga Samarinda. This student dispensation application is a website-based application that functions to make it easier for students to do permits while at the same time making it easier for the student waka kesiswaan to give permission to students without having to come to the room and reduce paper use. For analysis and application design using several tools, namely: Use Case diagrams, Activity diagrams, Sequence diagrams and Class diagrams. As for the system development method using the waterfall method. This application was built using Visual Studio Code based on the PHP programming language, for database management using MySQL. Besides that, the Black Box method is used as a system testing method to find out all functions can run properly.